Sumber Landasan dalam Merumuskan kaidah-kaidah Nahwu dan Signifikansinya untuk Pembelajaran Bahasa Arab - Muhammad Rizal; Maman Abdurrahman; Asep Sopian (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
The nahwu rules that have been studied and known so far do not necessarily exist and have previously been available, but this is the result of the hard work of linguists using a variety of methods in it. This study aims to reveal the bases used by linguists in the formulation and standardization of nahwu rules. The type of method used in this study is a qualitative research method using a library research approach. Based on the analysis of the literature study, the linguists use four main bases in formulating the rules of nahwu, including the samā’ or naql, ijmā', qiyās and istiṣḥāb. Samā ' has three main foundations in the form of definite arguments in building nahwu rules, al-Qurān, the hadīth, and the words of the Arabs, both in the form of verse and prose. Ijmā’ is an agreement of language scholars in compiling nahwu rules. Qiyās is the largest argument used by linguists in making rules and for solving linguistic problems that arise. The last is the istiṣḥāb; although it is the weakest foundation compared to the others, it is still used in determining the nahwu rules. Knowing these all aspects will give many benefits in teaching and learning Arabic.